2014
DOI: 10.1002/ajim.22391
|View full text |Cite
|
Sign up to set email alerts
|

Life‐span carcinogenicity studies on Sprague–Dawley rats exposed to γ‐radiation: Design of the project and report on the tumor occurrence after post‐natal radiation exposure (6 weeks of age) delivered in a single acute exposure

Abstract: Our data show that exposure to γ-radiation induces carcinogenic effects at all tested doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The dose of the positive controls (0.1 Gy) was selected so as to have a comparison with the results of a previous larger experiment on the carcinogenicity of γ radiation, in which the lowest dose tested was 0.1 Gy. 31 The results of the study are reported in Tables 5-8. Table 5 shows that exposure to 1000 μT S-50 Hz MF plus 0.1 Gy induces a statistically significant dose-related increase (P ≤ 0.01) in males bearing malignant tumours compared to negative controls, in particular at the highest…”
Section: Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose of the positive controls (0.1 Gy) was selected so as to have a comparison with the results of a previous larger experiment on the carcinogenicity of γ radiation, in which the lowest dose tested was 0.1 Gy. 31 The results of the study are reported in Tables 5-8. Table 5 shows that exposure to 1000 μT S-50 Hz MF plus 0.1 Gy induces a statistically significant dose-related increase (P ≤ 0.01) in males bearing malignant tumours compared to negative controls, in particular at the highest…”
Section: Groupmentioning
confidence: 99%
“…All the four experimental groups encompassed 1658 rats. The dose of the positive controls (0.1 Gy) was selected so as to have a comparison with the results of a previous larger experiment on the carcinogenicity of γ radiation, in which the lowest dose tested was 0.1 Gy . The results of the study are reported in Tables 5‐8.…”
Section: Introductionmentioning
confidence: 99%